SOME NEW RESULTS ON SEMITOTAL-BLOCK GRAPHS - Shetty, Jayashree B. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In this paper, we obtain characterization of graphs is 3- minimally nonouterplanar in terms of forbidden sub-graphs. In addition, we present characterization of graphs whose semitotal-block graph is n-minimally nonouterplanar and also 2n-minimally nonouterplanar.